Touring America's national parks (Chicago, IL : Questar, 2009)
Looks at twenty of the country's most popular national parks.
Not rated.
DVD.
Keywords: National parks and reserves -- United States; United States -- Description and travel; Nonfiction films; Travel programs; Feature films